(untitled) (Ustozlar uchun, 2025)
ABSTRACT The rapid increase in global energy consumption and greenhouse gas emissions has led to an urgent need for sustainable and clean energy systems. Renewable energy sources (RES) — including solar, wind, hydro, biomass, and geothermal — play a crucial role in mitigating climate change by reducing reliance on fossil fuels. This study explores the role of renewable energy sources in decreasing greenhouse gas (GHG) emissions from technological, economic, and environmental perspectives. The focus is placed on Uzbekistan, a nation undergoing significant energy transformation through its “Yangi Energiya” strategy and large-scale solar and wind projects. Key examples include the 100-MW Navoi Solar Power Plant and the 500-MW Zarafshan Wind Farm, both contributing to national CO₂ reduction goals. Using data from the International Energy Agency (IEA), World Bank, and Uzbekenergo, this research analyzes how renewable investments improve energy efficiency, reduce carbon intensity, and foster sustainable economic growth. The findings confirm that renewable energy adoption not only cuts emissions but also enhances energy independence, job creation, and long-term environmental stability.